Social Skills Interventions for Students With Challenging Behavior: Evaluating the Quality of the Evidence Base. (January 2017) - Hutchins, Nancy S.; Burke, Mack D.; Hatton, Heather; Bowman-Perrott, Lisa
This study provides results on a methodological quality review of the single-case research literature from 1998 to 2014 on the use of social skills interventions for students with challenging behavior. A systematic review of the social skills literature was conducted with the intent of updating the Mathur et al. study of social skills interventions. Twenty-four studies, published between 1998 and 2014, were identified and coded for methodological quality. Findings indicated half the studies failed to meet single-case design standards. Many studies did not sufficiently report reliability, implementation fidelity, or provide adequate opportunities to demonstrate intervention effect. The three most common behaviors across all studies were noncompliance, negative verbal interactions, and class disruptions. The majority of studies were conducted in early elementary grades. Results are discussed in the context of the need for greater methodological rigor for future single-case research studies in the area of social skills instruction.